2023
DOI: 10.1088/1367-2630/acae3c
|View full text |Cite
|
Sign up to set email alerts
|

Rotational mirror–mirror entanglement via dissipative atomic reservoir in a double-Laguerre–Gaussian-cavity system

Abstract: We propose a new scheme to prepare macroscopic entanglement between two rotating mirrors using dissipative atomic reservoir in a double-Laguerre-Gaussian-cavity (DLGC) system. The two-level atomic system driven by a strong field, acts as a single pathway of Bogoliubov dissipation to push the two original cavity modes into the desirable entangled state under the near-resonant conditions. Successively, the photon-photon entanglement can be transferred to mirror-mirror entanglement through the exchange of orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…And the nonlocal correlation of macroscopic objects can be widely used in large-scale fundamental testing of quantum mechanics, quantum to classical transitions, and building more powerful sensing, communication, processing, and storage devices [18][19][20]. In cavity optomechanics, significant progress has been made in the study of macroscopic entanglement via the optomechanical radiation pressure [21], where the entanglements of two distant macroscopic mechanical resonators and between the massive mechanical oscillator and the electromagnetic field or collective atomic spin oscillator have been reported [22][23][24][25][26]. Apart from the optomechanical system, cavity magnonics has gradually become an advantageous platform for studying macroscopic quantum entanglement [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…And the nonlocal correlation of macroscopic objects can be widely used in large-scale fundamental testing of quantum mechanics, quantum to classical transitions, and building more powerful sensing, communication, processing, and storage devices [18][19][20]. In cavity optomechanics, significant progress has been made in the study of macroscopic entanglement via the optomechanical radiation pressure [21], where the entanglements of two distant macroscopic mechanical resonators and between the massive mechanical oscillator and the electromagnetic field or collective atomic spin oscillator have been reported [22][23][24][25][26]. Apart from the optomechanical system, cavity magnonics has gradually become an advantageous platform for studying macroscopic quantum entanglement [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[56,57] Furthermore, researchers used a hybrid rotational system to study OMIT, [58][59][60][61][62] cooling of rotating mirrors, [63] and entanglement. [64][65][66][67] Most recently, there is an interesting study by Huang et al, in which they proposed an LG cavity optomechanical scheme, assisted with an optical parametric amplifier (OPA). [68] They used the pump frequency of the OPA which is double the frequency of the anti-Stokes field generated by the external laser beam interacting with both rotating mirrors.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, optomechanical systems, in which a cavity field is coupled with a macroscopic mechanical oscillator via linear momentum transfer, have been proven to be a promising platform on which to prepare macroscopic entanglement [5] because the linear vibration of the mechanical oscillator can, experimentally, be cooled down close to its quantum ground state [6,7]. Meanwhile, Laguerre-Gaussian-(LG)-cavity optomechanical systems have been intensively studied [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In these, an LG-cavity mode is coupled to a rotating mirror due to the orbital angular momentum transfer from the LG-cavity mode to the rotating mirror.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that it is also possible to cool down the rotational motion of a macroscopic mirror close to its quantum ground state [8]. Thus, it is possible to observe a variety of nonlinear and quantum phenomena in such systems, including optomechanically induced transparency [9][10][11][12], optomechanically induced amplification [13], Fano resonance [14], fast and slow light [11,14], optical sum-sideband generation [15], second-order sideband effects [16], entanglement between an LG-cavity mode and a rotating mirror [17,18], stationary entanglement between two rotating mirrors [19,20], and tripartite entanglement between an LG-cavity mode, a magnon mode, and a phonon mode [21].…”
Section: Introductionmentioning
confidence: 99%